2018
DOI: 10.1021/acs.jmedchem.8b00770
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 4-Hydroxy-3-(3-(phenylureido)benzenesulfonamides as SLC-0111 Analogues for the Treatment of Hypoxic Tumors Overexpressing Carbonic Anhydrase IX

Abstract: Herein we report the 2-aminophenol-4-sulfonamide 1 and its ureido derivatives 2-23 as inhibitors of the carbonic anhydrase (CA, EC 4.2.1.1) enzymes as analogues of the hypoxic tumor phase II entering drug SLC-0111. This scaffold may determine preferential rotational isomers to selectively interact within the tumor-associated CAs. Most of the compounds indeed showed in vitro selective inhibition of the tumor associated CA isoforms IX and XII. The most potent derivative within the series was 11 ( Ks of 2.59 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…8. General Procedure for the Synthesis of compound [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. A solution of 5a-b (0.2 g, 1.0 eq) in dry MeOH was treated with Et 3 N (1 eq) then the reaction mixture was cooled to 0 • C and benzaldehyde 6-15 (1 eq) was added.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…8. General Procedure for the Synthesis of compound [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. A solution of 5a-b (0.2 g, 1.0 eq) in dry MeOH was treated with Et 3 N (1 eq) then the reaction mixture was cooled to 0 • C and benzaldehyde 6-15 (1 eq) was added.…”
Section: Chemistrymentioning
confidence: 99%
“…An important structural consideration is the role of the linker connecting the tail and the warhead sections within CAI molecules in order to make use of the tail strategy. The ureidic moiety was demonstrated to be particularly suitable as it allows the entire molecule to assume the best conformation when allocated within the enzyme cavity and at the same time to contribute to the stabilization of the enzyme-inhibitor complex by means of hydrogen bonds [8][9][10][28][29][30]. Subsequently, various CAI moieties bearing ureido linkers were reported [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA inhibitors (CAIs) are used to treat a variety of diseases such as glaucoma, altitude sickness, and epilepsy [9]. In addition, CAIs are currently being developed as anti-cancer drugs [10][11][12]. These inhibitors are designed to bind to the active site zinc, displacing the zinc bound solvent.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above [6,[16][17][18][19], several CA isoforms are predominantly present in tumors, in which they are involved in pH regulation and metabolic processes. It has been demonstrated that their specific inhibition with sulfonamides, sulfamates, or coumarins [56][57][58][59] has profound effects on the inhibition of the primary tumor growth, metastases formation and reduction in the cancer stem cells number, three mechanisms unique only to this class of pharmacological agents [60][61][62]. Thus, a large number of drug design studies were performed in the last 10 years for the design of CA IX/XIIselective inhibitors [1,[3][4][5][6]55], with one such compound, SLC-0111 presently in Phase Ib/II clinical trials as an antitumor/antimetastatic agent [63].…”
mentioning
confidence: 99%